2021
DOI: 10.1371/journal.pone.0255262
|View full text |Cite
|
Sign up to set email alerts
|

Genomic diversity of bacteriophages infecting Rhodobacter capsulatus and their relatedness to its gene transfer agent RcGTA

Abstract: The diversity of bacteriophages is likely unparalleled in the biome due to the immense variety of hosts and the multitude of viruses that infect them. Recent efforts have led to description at the genomic level of numerous bacteriophages that infect the Actinobacteria, but relatively little is known about those infecting other prokaryotic phyla, such as the purple non-sulfur photosynthetic α-proteobacterium Rhodobacter capsulatus. This species is a common inhabitant of freshwater ecosystems and has been an imp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“… Rhodobacter capsulatus , a freshwater alphaproteobacterium, was the first microorganism found to perform horizontal gene transfer with a bacteriophage-like gene transfer agent (RcGTA) ( 1 ). Recent studies found that many bacteriophages that infect this host share genes with RcGTA ( 2 6 ). Prior to this announcement, 29 R. capsulatus phage genomes were organized into six distinct clusters (RcA to RcF), with four remaining as singletons ( 2 ).…”
Section: Announcementmentioning
confidence: 99%
See 2 more Smart Citations
“… Rhodobacter capsulatus , a freshwater alphaproteobacterium, was the first microorganism found to perform horizontal gene transfer with a bacteriophage-like gene transfer agent (RcGTA) ( 1 ). Recent studies found that many bacteriophages that infect this host share genes with RcGTA ( 2 6 ). Prior to this announcement, 29 R. capsulatus phage genomes were organized into six distinct clusters (RcA to RcF), with four remaining as singletons ( 2 ).…”
Section: Announcementmentioning
confidence: 99%
“…Recent studies found that many bacteriophages that infect this host share genes with RcGTA ( 2 6 ). Prior to this announcement, 29 R. capsulatus phage genomes were organized into six distinct clusters (RcA to RcF), with four remaining as singletons ( 2 ). To advance our understanding of these phages and RcGTA, we have expanded this collection with 24 genomes from isolates collected throughout the state of Illinois.…”
Section: Announcementmentioning
confidence: 99%
See 1 more Smart Citation